1998
DOI: 10.1016/s0304-3959(98)00064-5
|View full text |Cite
|
Sign up to set email alerts
|

A placebo-controlled randomized clinical trial of nortriptyline for chronic low back pain

Abstract: To assess the efficacy of nortriptyline, a tricyclic antidepressant, as an analgesic in chronic back pain without depression, we conducted a randomized, double-blind, placebo-controlled, 8-week trial in 78 men recruited from primary care and general orthopedic settings, who had chronic low back pain (pain at T-6 or below on a daily basis for 6 months or longer). Of these 57 completed the trial; of the 21 who did not complete, four were withdrawn because of adverse effects. The intervention consisted of inert p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
118
0
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(122 citation statements)
references
References 23 publications
1
118
0
3
Order By: Relevance
“…Despite some progress, clinical treatment of pain and depression has so far been limited to symptomatic management (3, 36). A number of studies have also suggested that the effect of antidepressants on chronic pain is not necessarily related to their anti-depression property (36)(37)(38).…”
Section: Figurementioning
confidence: 99%
“…Despite some progress, clinical treatment of pain and depression has so far been limited to symptomatic management (3, 36). A number of studies have also suggested that the effect of antidepressants on chronic pain is not necessarily related to their anti-depression property (36)(37)(38).…”
Section: Figurementioning
confidence: 99%
“…87 Studies with amitryptiline, nortriptyline, and maprotiline demonstrated analgesic ESs ranging from 0.45 to 0.64. [88][89][90] A meta analysis by Salerno and colleagues revealed that antidepressants had a small but statistically significant effect in reducing LBP when compared with placebo. Patients treated with antidepressants experienced a small but significant improvement of 0.41 (95% confidence interval [CI], 0.22-0.61) in the standardized mean difference for pain severity.…”
Section: (Continued)mentioning
confidence: 99%
“…While antidepressants affect mood changes in chronic pain patients, they do not always improve outcome measures of clinical pain (Littlejohn, Guymer, 2006;Carter 2002). In this regard, several studies have suggested that the effect of antidepressants on chronic pain may not be related to their antidepression property (Atkinson et al, 1998;Collins et al2000;Max et al, 1987;Mico et al, 2006;Sharav et al, 1987). To date, the relationship between pain and depression remains unclear.…”
Section: Introductionmentioning
confidence: 99%